Development of Augmented Reality Learning Media on Virus Material (ARBioVirus) for Class X - Fatmawati, Putri; Sari, Tika Mayang (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2024)
This study was initiated due to the limited availability of diverse learning materials in schools, impacting students' engagement and enthusiasm in learning about viruses. The primary objective of this research was to create augmented reality learning resources focused on the topic of viruses, evaluating both the practicality and the response to the developed educational content. The research employed the Research and Development (R&D) approach, utilizing the ADDIE research model, which encompasses five key stages: Analysis, Design, Development, Implementation, and Evaluation. The findings, based on assessments from material and media experts, revealed a high level of feasibility for the augmented reality learning media. Material experts declared a 88.8% feasibility, while media experts indicated an 82.5% feasibility. Moreover, the responses from students and biology teachers at SMA Negeri 5 Metro indicated positive feedback, with 86.66% of students considering the learning media as